2014
DOI: 10.1519/jsc.0000000000000328
|View full text |Cite
|
Sign up to set email alerts
|

Use of Heart Rate Variability in Monitoring Stress and Recovery in Judo Athletes

Abstract: The main objective of this study was to examine the effect of different judo training loads on heart rate variability (HRV) measurements, to determine if they can be used as valid indicators in monitoring stress and recovery in judo athletes. Fourteen male national-standard judo athletes were randomly divided into 2 groups, and each group followed a different type of training, namely, a high training load (HTL) and a moderate training load program (MTL). Data collection included HRV measurements, a Recovery St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 35 publications
0
50
0
6
Order By: Relevance
“…A common issue with traditional HRV methodology is the requirement for lengthy recording procedures under laboratory controlled settings with specialized equipment, such as electrocardiograms [13,18]. Furthermore, it has recently been suggested that training adaptation is more strongly related to weekly mean values of HRV compared to isolated recordings, primarily due to high day-to-day variability, or coefficient of variation (CV), in ANS activity [8,26,29]. These necessities make convenient HRV recordings and data analysis in applied sport settings nearly impossible.…”
mentioning
confidence: 99%
“…A common issue with traditional HRV methodology is the requirement for lengthy recording procedures under laboratory controlled settings with specialized equipment, such as electrocardiograms [13,18]. Furthermore, it has recently been suggested that training adaptation is more strongly related to weekly mean values of HRV compared to isolated recordings, primarily due to high day-to-day variability, or coefficient of variation (CV), in ANS activity [8,26,29]. These necessities make convenient HRV recordings and data analysis in applied sport settings nearly impossible.…”
mentioning
confidence: 99%
“…La primera, titulada "El uso de la variabilidad de la frecuencia cardiaca como variable de control del entrenamiento en judocas" fue realizada por el Dr. Manuel Moya Ramón, profesor de la Facultad de Ciencias del Deporte de la Universidad Miguel Hernández de Elche. En ella se habló sobre la utilidad del uso de la variabilidad de la frecuencia cardiaca como una herramienta eficaz que permite cuantificar el impacto producido en el organismo por una sesión de entrenamiento, facilitando de ese modo la capacidad de adaptar la carga de entrenamiento en función del estado de recuperación del deportista (Morales et al, 2014). El uso de la variabilidad de la frecuencia cardiaca permite realizar un seguimiento a medio-largo plazo del proceso de entrenamiento de forma fácil y cómoda, utilizando nuestro teléfono móvil como herramienta de trabajo mediante el uso de aplicaciones como HRV4Training ® o Elite HRV ® .…”
Section: Ponencias Plenariasunclassified
“…On the other hand, the reduction in perceived stress due to relaxing techniques has been shown to be associated with an increase in HR autonomic modulation [23][24][25]. HRV parameters are nowadays used also as tools for monitoring athletes' psychophysiological condition and training status [26,27].…”
Section: Introductionmentioning
confidence: 99%